P-165 An Electronic Health Record Tool Improves Safety and Efficiency of Infliximab Prescribing. (February 2017) - Gjikopulli, Arieda; Hilmas, Elora; Sharpless, Bethany; Molle-Rios, Zarela
Abstract : Background: Infliximab is a chimeric monoclonal antibody against tumor necrosis factor α approved for the induction and maintenance of remission in Crohn's disease and ulcerative colitis. Adoption of Electronic Health Record (EHR) has recently widespread and almost 3 of 4 physicians report using EHR. EHR can improve our ability to order and monitor infliximab therapy. Appropriate dosing and monitoring of this high-cost medication involves reviewing various patient-specific factors through various sections of the medical chart. The current practice of infliximab ordering in our institution was liable to errors secondary to communication breakages between the primary gastroenterologist and the provider entering the infliximab prescription. Using the EHR, an interactive flow sheet was developed that retrieves critical data into one location in the chart and allows for communication between practitioners viewing the flow sheet. Our objective is to assess the utility of this tool by auditing the tool usage and if it resulted in proper communication and to investigate the providers' perception of the tool's impact on improved safety and efficiency. Methods: A novel interactive cross-encounter flow sheet that collected data from the EHR was designed by pharmacy, informatics and was vetted by the gastroenterology providers. Data gathered in the flow sheet includes weight, BMI, infliximab dose, infliximab level and antibodies to infliximab, PPD status, last office visit date and medication history. In addition, a questionnaire was created that allowed physicians to communicate plans for intended infliximab dose and frequency changes as well as additional comments regarding infusion and special laboratory tests to be obtained at the time of infusion. Data entered into the questionnaire were automatically populated into the flow sheet. Providers received education and training on using the above tools and a new workflow was introduced where the flow sheet was reviewed prior to each infliximab prescribing. Data entry frequency through the questionnaire was quantified. A preliminary audit was completed on 14 random occasions that the questionnaire was used; each patient chart was reviewed to assess if instructions or changes entered were executed accordingly. Data was collected from December 1, 2015 to April 1, 2016. A survey 8 months post the tool implementation was performed to assess its value. Descriptive statistics were used. Results: There were 107 data entries made through the questionnaire during this 4-month period and 60% of the gastroenterology providers used this tool. Chart auditing revealed that in 12 of 14 occasions that the EHR tool was used resulted in successful implementation of each instructed change or request. The post-implementation survey was completed by 10 of 13 GI providers. Hundred percent of providers stated that they plan continuing to use the tool. Additionally, 90% and 100% stated that the tool improved the safety and efficiency of infliximab prescribing respectively. Conclusions: The implementation of this infliximab therapy cross-encounter flow sheet and questionnaire has facilitated the communication of pertinent infliximab ordering information. Ordering physicians reported that this tool improves the safety and efficiency of infliximab ordering.